Harmonizing core competencies for Master of Public Health Training programmes in Africa - Opare, Abraham (Department of Public Health and Family Medicine, 2026)
Africa faces numerous health challenges, including high burdens of diseases and fragile health which hinder efforts to prevent, address, mitigate, and control these health challenges. The skills taught in MPH programs are recognized globally as being crucial to addressing these challenges and strengthening health systems. In recent years, the global community has experienced the emergence and re-emergence of disease outbreaks such as the Ebola and COVID-19 pandemics. These outbreaks have highlighted the need to strengthen programs like the MPH to equip graduates with the competencies necessary to address new and emerging health challenges. Additionally, they have highlighted the shared health systems challenges faced by different countries in Africa and the vulnerability of health systems to new challenges. The Association of Schools of Public Health in Africa (ASPHA) has acknowledged the lack of harmonization in the training received by MPH students from the different MPH programs on the continent. This lack of harmonization in MPH training within and across African countries has been attributed to the absence of a core competency framework, which outlines the competencies relevant to the public health work undertaken by MPH graduates in the region. Aim: This thesis identified the set of core competencies that are relevant to the public health work undertaken by MPH graduates across different work settings in Africa, including the challenges that could be encountered in adopting harmonized or common sets of core competencies across MPH programs in Africa Methods: A structured literature review was conducted to identify a preliminary set of core competencies for MPH programs in Africa. These competencies were subsequently refined through stakeholder engagement, resulting in a more focused and contextually relevant set of competencies that guided interviews with key informants. In order to elicit information from a broad range of country contexts, fieldwork was conducted in five African universities: one South African university (the University of Cape Town), in two Ghanaian universities (University of Ghana, Kwame Nkrumah University of Science and Technology); in one Nigerian university (University of Ibadan), and one Kenyan university (Great Lakes University of Kisumu). In each university, MPH graduates were surveyed to determine the applicability of competencies identified in the structured literature review to their work, the contribution of the MPH to competencies development, and graduates' level of confidence with each competence. Lecturers were interviewed and MPH curricula documents were reviewed to determine the depth of coverage of competency domains considered to be core in the five MPH programs. In-depth interviews were used to explore the perspective of a range of employers of MPH graduates from fourteen African countries on the actual sets of core competencies graduates need for public health work in Africa. Finally, interviews and surveys with lecturers and heads of MPH programs were used to explore the challenges that MPH programs in Africa could face in adopting harmonized or common set of core competencies across programs. Findings: A preliminary set of competencies – 187 competencies across nine discipline- specific and seven cross-cutting domains were identified for MPH programs in Africa through the literature review. Importantly, domains such as public health law and outbreak management which provides the foundation for creating equitable health systems and addressing emerging epidemics and pandemics, are missing from most MPH programs in Africa. Additionally, competencies in domains such as leadership, communication, monitoring and evaluation, community and intersectoral collaboration, outbreak management, and health promotion are the most applicable to graduates' work despite MPH programs contributing minimally to their development among graduates. Furthermore, the results show that while MPH programs in Africa generally equip graduates with foundational knowledge and skills in domains like Epidemiology, Biostatistics, Health Systems, Policy and Management, Health Promotion, Environmental Health Science, and Social and Behavioural Science, few programs provided graduates with the platform/opportunity to apply this knowledge and skills to real-life public health work during their MPH training. Across different African country settings, employer interviews found that MPH graduates in Africa perform critical roles that contribute significantly to health systems strengthening and were instrumental in the public health response to the COVID-19 pandemic. Employers reported that competencies in technical domains such as data analysis and interpretation, research proposal development, research grant application, outbreak management, public health-related law, teaching & coordination of health training programs, health promotion & advocacy, health resource mobilization, monitoring and evaluation, environmental health, Health financing and budgeting, and project management are crucial to the work of MPH graduates in Africa. Additionally, they emphasized that soft skills, including leadership, good time management, teamwork, conflict management, and communication and dissemination of public health information using tools like PowerPoint are important to the work of MPH graduates in Africa. Challenges to adopting harmonized or common sets of core competencies across Africa include institutional differences, chiefly regarding resources and culture, bureaucratic hurdles with integration into curriculums, resistance from faculty members, and resource limitations. Conclusion: This thesis used mixed methods in five different country settings, to identify the set of core competencies that are relevant to the public health work undertaken by MPH graduates in Africa. Challenges of adopting harmonized or common sets of competencies across MPH programs in Africa are identified. While competencies in key domains such as epidemiology, biostatistics, and research are already emphasized in most MPH programs in Africa, competencies in other key domains such as outbreak management, leadership, public health-related law communication, monitoring and evaluation, health financing, and project management are less emphasized or missing in most MPH programs in the region and need attention. There is a need for curriculum reforms among MPH programs in Africa to ensure that crucial and practical competencies are included or emphasized in MPH programs to better prepare graduates to effectively tackle the continent's health system challenges. A key limitation of the study was the limited representation of Francophone countries. Future work could explore competency frameworks in non-ASPHA and Francophone contexts and focus on building consensus among MPH education stakeholders in Africa on which competencies identified in this thesis should be included in MPH curricula. Future work could also focus on creating a core competency framework for MPH programs in Africa using the findings from this thesis as a guide.